Digitally Driven Interdisciplinary Smile Redesign in a Patient with Midline Deviation: A Case Report - Alinda, Ruri Nur; Indra, Putu; Hadinata, Ferdinand; Satyaputra, Made Dwiandri; Ayub, Aulia; Alhasyimi, Ananto Ali (European Journal of Dentistry, 2025)
A 29-year-old woman with midline deviation (maxillary dental midline was shifted 4.3 mm to the right side) and unsightly anterior veneers placed by an unlicensed dental professional, resulting in poor esthetic outcomes. Clinical findings included incorrect occlusion, asymmetric gingival contours, and overcontoured veneers. A multidisciplinary treatment strategy was created to rectify midline deviation and restore esthetics. This included the expertise of orthodontists, periodontists, endodontists, and restorative professionals. The patient underwent a series of treatments, starting with orthodontic realignment to correct occlusion and midline deviation, followed by periodontal intervention to address asymmetric gingival contours, and finally, restorative procedures involving facially directed zirconia veneers. Posttreatment, the dental midline was realigned toward the facial flow line, significantly improving smile symmetry and occlusal function. The patient reported high satisfaction with the outcome, particularly regarding the harmony between her dental and facial features. This case highlights the effectiveness of a digitally driven, interdisciplinary approach to correct complex esthetic issues following poor dental restorations. Three-dimensional facial scanning, in combination with orthodontic, periodontal, endodontic, and restorative treatments, provided precise and predictable results, leading to a highly successful outcome and improved patient satisfaction.This technique has the following advantages:
Keywords: 3D facial scan; midline deviation; crown lengthening; interdisciplinary dentistry; patient satisfaction